Artificial Intelligence Powering Internet of Things - Vijaykumar, Suhasini; Yadav, Avinash (International Journal of Computer Sciences and Engineering, 2019)
The IOT concept came into existence in 1999 and from there it has grown into one of the most important parts of the new fields and technologies sector. Artificial Intelligence being included to the IOT systems is the next step and it is being used in daily life. This technology is used in various fields and it is a wide range concept which can be used anywhere. Artificial intelligence is the first and most popular option to manipulate huge data outflow and storage within the IOT community. Currently IOT is most popular with cutting edge sensors and high speed internet which are all included in a microcontroller. The streams of data flowing through Internet gather sensor and customer data which are sent and attain by terminals or workstations. With sudden popularity of cutting edge sensors and workstations, some data can have problems on storage, delays, routing problems with its network traffic etc. To avoid all these problems, many techniques have been recommended in the past 4 years and in that AI algorithms are the most accurate solution to the data mining, management and control in handling network traffic. When the Internet of Things is power-driven by AI, then it is known as Intelligent IOT. In this paper we will review the basic components of Intelligent IOT and some vital system fields where it is used. We examine the role of AI strategies to enable such networks with intelligent communication. This paper is targeted on evaluating current solutions for the intelligent IOT connected and communicating with each other. It conveys AI techniques and algorithms which are used to create such intelligent IOT, and network solutions to use the advantages given by such capabilities.